(untitled) (Bangladesh Journal of Medical Science, 2025)
Food security, defined as consistent access to sufficient, safe, and nutritious food, is crucial in shaping community health. This scoping review explores the multidimensional impacts of food security on physical, mental, and social well-being. Malnutrition, stemming from both undernutrition and overnutrition, links food insecurity to health issues such as stunted growth, obesity, and chronic diseases like diabetes and heart conditions. Moreover, the psychological toll of food insecurity is significant, manifesting as stress, anxiety, and depression while exacerbating social inequalities and perpetuating cycles of poverty and ill health. Global and national perspectives reveal the persistent challenge of food insecurity, particularly in low- and middle-income regions, where economic disparities, climate change, and conflicts disrupt food systems. In Malaysia, rising food insecurity has highlighted gaps in nutrition quality and affordability, with vulnerable groups, including children and low-income households, experiencing the brunt of its effects. Addressing food security requires sustainable agricultural practices, effective policies, and robust social safety nets. National initiatives, such as Malaysia’s Agrofood Policy 2021-2030, focus on enhancing food self-sufficiency, supporting farmers, and fostering sustainable practices through technology and education. However, challenges such as aging agricultural populations, land limitations, and climate variability remain barriers. This paper underscores the importance of holistic approaches to food security, integrating nutrition education, mental health support, and economic interventions to foster healthier, more resilient communities. Food security is essential for improving public health and achieving broader socioeconomic stability and sustainable development Bangladesh Journal of Medical Science Vol. 24 No. 02 April’25 Page : 307-330